Study on the Influence of mRNA, the Genetic Language, on Protein Folding Rates - Li, Ruifang; Li, Hong; Feng, Xue; Zhao, Ruifeng; Cheng, Yongxia (Frontiers in Genetics, 2021)
Many works have reported that protein folding rates are influenced by the characteristics of amino acid sequences and protein structures. However, few reports on the problem of whether the corresponding mRNA sequences are related to the protein folding rates can be found. An mRNA sequence is regarded as a kind of genetic language, and its vocabulary and phraseology must provide influential information regarding the protein folding rate. In the present work, linear regressions on the parameters of the vocabulary and phraseology of mRNA sequences and the corresponding protein folding rates were analyzed. The results indicated that D2 (the adjacent base-related information redundancy) values of the corresponding mRNA sequences exhibit significant positive relations with the protein folding rates, but for parameter D1 (the single base information redundancy), the correlations with the folding rates of the two-state folders are the opposite of the correlations of the multistate folders; furthermore, the GC content values exhibit significant negative relations with the protein folding rates. In addition, the results show that the relationships between the parameters of the genetic language and the corresponding protein folding rates are obviously different for different protein groups. Some useful parameters that are related to protein folding rates were found. The results indicate that when predicting protein folding rates, the information from protein structures and their amino acid sequences is insufficient, and some information for regulating the protein folding rates must be derived from the mRNA sequences.